Pengaruh Kompetensi Auditor Internal, Time Budget Pressure, dan Kecerdasan Emosional terhadap Pengungkapan Fraud : (Studi Kasus pada Kantor Pegadaian Oesapa, Kota Kupang, Nusa Tenggara Timur) - Yumitra Rambu Dawi Ngana; Anthon S. Y. Kerihi; Nikson Tameno (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the significance level of the influence of minimum wages and inflation on labor absorption in Indonesia over the period 1993–2023. Using a quantitative approach with a field research design, the study relies on secondary time-series data published by the Central Bureau of Statistics (BPS). Data were collected through documentation methods and analyzed using multiple linear regression with EViews 12 software. The results reveal that, partially, the minimum wage variable has a positive and significant effect on labor absorption, indicating that higher minimum wages contribute to increased employment absorption during the study period. Conversely, the inflation variable, while positively related to labor absorption, does not show a statistically significant effect, suggesting that rising inflation alone does not directly influence employment opportunities. Simultaneously, minimum wages and inflation together exert a significant joint effect on labor absorption. These findings underscore the importance of adaptive minimum wage policies that consider inflation trends to balance workers’ welfare with sustainable employment, thereby maintaining labor market stability in Indonesia.